Change Education: Warp of Aspirations and Contradictions - Margarita Zorrilla Fierro (Universidad Autónoma de Madrid, 2018)
Changing education to achieve a human world, more just and fraternal, continues to be an ideal current in our days. For now, it would seem simple to ask about the reasons that support this ideal that we inherit from the Enlightenment; However, it is not.